Analysis of SDIDTK Implementation Factors in the Karanganyar Community Health Center Working Area - Zuiatna, Dian; Suwardi, Suyanti; Nasution, Pratiwi (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Age less than five years is an important period in the growth and development of a child which influences and determines the child's future development. Early stimulation is stimulation that is carried out in the womb and is carried out every day to stimulate the entire sensory system of hearing, sight, touch, smell and taste. This is an activity that aims to stimulate the basic abilities of children aged 0-6 years so that they can grow and develop optimally. Lack of stimulation can result in abnormalities in a child's growth and development, and can even cause permanent problems. Increasing the quality of under-five children will be achieved by implementing SDIDTK which is well coordinated and comprehensive. Achieving SDIDTK activities for toddlers is the role of medical personnel. Midwives are the ones who determine and are responsible for achieving SDIDTK success in toddlers. The aim of this research is to analyze factors in implementing SDIDTK in the Karanganyar Health Center Work Area. This research uses a quantitative approach method with a cross sectional design using the chi-square test and multiple logistic regression test. Knowledge is the most dominant factor influencing the implementation of SDIDTK in the Karanganyar Health Center Work Area.